Hospital Onset Staphylococcus aureus Bacteremia is a Better Measure than MRSA Bacteremia in Assessing Infection Prevention: Evaluation of 51 US Hospitals. (4th October 2017) - Fakih, Mohamad; Battjes, Rebecca; Sturm, Lisa; Jones, Lindsey; Groves, Clariecia; Bufalino, Angelo; Hendrich, Ann
Abstract: Background: Hospital Onset (HO) Methicillin-resistant Staphylococcus aureus (MRSA) bacteremia is publicly reported and tied to the Hospital-Acquired Conditions Reduction program. It reflects a surrogate of risk of infection of MRSA invasive disease in the hospital setting, and reported as a standardized infection ratio that adjusts for admission MRSA prevalence, hospital size and medical school affiliation. However, it may not adequately represent all HO S . A ureus bacteremia, which is unaffected by the prevalence of resistance to methicillin. Methods: We compared the rates of NHSN-defined laboratory ID events for HO methicillin susceptible S . A ureus (MSSA) and MRSA bacteremia in 51 hospitals (small, <100 beds, n = 15; medium, 100–300 beds, n = 15; large, >300 beds, n = 21) from a single health system over a 12-month period abstracting data from one clinical decision support system. We also compared the rates of HO S . A ureus bacteremia based on hospital size. Results: 340 HO S . A ureus bacteremia events (1.22 per 10, 000 patient-days) occurred during calendar year 2016 (MSSA n = 218, 64%; MRSA n = 122, 36%). 14/15 small hospitals did not have any HO S . A ureus bacteremia events during the study period. HO MSSA bacteremia rates were 0.58 and 0.77 per 10, 000 patient-days for medium size and large-size hospitals respectively ( P = 0.094). In contrast, HO MRSA bacteremia rates were 0.71 and 0.47 per 10, 000 patient-days for medium size and large-size hospitals respectively ( P = 0.045). There was no correlation between HO MSSA and MRSA bacteremia for large and medium size hospitals (Figure). Conclusion: By measuring only HO MRSA, a significant portion of patients with increased morbidity and mortality are overlooked. HO S . A ureus bacteremia may provide a better measure to use to evaluate invasive S . A ureus risk in the hospital setting, and would mitigate the MRSA prevalence factor. These findings are important when we evaluate policy related to what is considered a hospital acquired condition. Disclosures: All authors: No reported disclosures.